Pengaruh Kecerdasan Spiritual, Kecerdasan Intelektual, Kecerdasan Emosional, Dan Kecerdasan Sosial Terhadap Pola Pikir Generasi Z (Studi Kasus Pada Generasi Z Di Desa Ima’an) - Az-zahroh, Putri; Pardiman, Pardiman; Amin, Muh Sirojuddin (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This research explores how spiritual, intellectual, emotional, and social intelligence impact the mindset of Generation Z in Ima'an Village, focusing on individuals aged 17–27. Employing an explanatory method with a quantitative approach, the study utilizes descriptive statistics and multiple linear regression analysis to identify which independent variables significantly influence mindset. The results for Hypothesis 1 indicate that spiritual intelligence has a significant effect on the mindset of Generation Z in the village, as shown by a significance value of 0,001, which is below the 0,05 threshold. Meanwhile, Hypothesis 3 is rejected. For Hypothesis 4, emotional intelligence does not significantly influence mindset, as evidenced by a significance value of 0,555, which exceeds 0,05, leading to the rejection of this hypothesis. Furthermore, the F-test reveals that all independent variables together have a significant impact on the dependent variable, with a significance value of 0,001. Keywords: Spiritual Intelligence, Intellectual Intelligence, Emotional Intelligence, Social Intelligence, Generation Z Mindset.